"Putting people in charge of their own health and care?" Using meta‐narrative review and the example of online sexual health services to re‐think relationships between e‐health and agency. (3rd May 2019) - Baraitser, Paula; Cribb, Alan
Abstract: Introduction: Policy discussions reference ideas of informed and active users of e‐health services who gain agency through self‐management, choice and care delivered outside clinical settings. In this article, we aim to problematize this association by "thinking with" material from multiple disciplines to generate higher order insights to inform service development, research and policy. Methods: Drawing on meta‐narrative review methods, we gathered perspectives from multiple disciplines using an iterative process of expert consultation to identify seminal papers citation mapping, synthesis and peer review. Results: We identify six relevant paradigms from sociology, philosophy, health services research, public health, the study of social movements and computer studies. Bringing these paradigms together illuminates the contrasting epistemological and ontological framings that co‐exist in this area, including competing conceptualizations of e‐health technologies as: neutral tools for service delivery, mediators within complex and unpredictable clinical interactions and as agents in their own right. Discussion: There is a need for e‐health policy to recognize many human and non‐human actors, the blurred boundaries between them and the unpredictable and evolving interactions that constitute engagement with e‐health care. Established models for e‐health service development and policy making are not designed for this landscape. There is nothing to be gained by asking whether e‐health, in general, either "increases" or "decreases" agency. Rather specific types and aspects of e‐health have diverse effects and can be simultaneously enabling and disempowering, and be differentially experienced by differently positioned and resourced actors.